2020
DOI: 10.1037/trm0000228
|View full text |Cite
|
Sign up to set email alerts
|

In the aftermath: The effects of hurricanes Harvey and Maria on the well-being of health-care and social service providers.

Abstract: Health-care and social service providers affected by climate-related disasters play a pivotal role in response and recovery but yet are at a disproportionate risk for mental health symptoms such as posttraumatic stress disorder (PTSD), secondary traumatic stress, anxiety, and burnout. Factors such as social support and resilience may protect these providers from stress related symptoms. To explore providers' responses to recent disasters, this study examined mental health distress, work-related stress, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
15
1
Order By: Relevance
“…Social support has been shown to be predictive of improved mental health outcomes as well as reduced posttraumatic symptoms among veterans and survivors of disasters, whether the traumatic event takes the form or natural disasters or events such as war or assault (Pittman et al, 2020; Smith et al, 2014; Wilks et al, 2019). For example, within the context of traumatic stress from hurricanes, social support has also been found to be correlated with resilience and compassion satisfaction while being inversely related to burnout and anxiety (Powell et al, 2020). Rather than facing the difficulties associated with trauma alone, one can reduce the burdens, responsibilities, and stresses by receiving help, comfort, materials, or spiritual care.…”
Section: Social Support and Mental Health Outcomes Post Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Social support has been shown to be predictive of improved mental health outcomes as well as reduced posttraumatic symptoms among veterans and survivors of disasters, whether the traumatic event takes the form or natural disasters or events such as war or assault (Pittman et al, 2020; Smith et al, 2014; Wilks et al, 2019). For example, within the context of traumatic stress from hurricanes, social support has also been found to be correlated with resilience and compassion satisfaction while being inversely related to burnout and anxiety (Powell et al, 2020). Rather than facing the difficulties associated with trauma alone, one can reduce the burdens, responsibilities, and stresses by receiving help, comfort, materials, or spiritual care.…”
Section: Social Support and Mental Health Outcomes Post Traumamentioning
confidence: 99%
“…Individuals exposed to disasters may experience mental health consequences such as posttraumatic stress disorder (PTSD), grief, depression, anxiety, stress-related health problems, increased substance abuse, and suicidal ideation (Bonanno et al 2010; Long et al, 2020), but these outcomes are not just limited to survivors of the trauma itself. They can extend to health-care workers who provide aid to those affected (Powell, 2020). PTSD, in particular, is a common consequence of disasters (Bistricky et al, 2019; Neria et al, 2008).…”
mentioning
confidence: 99%
“…Given our findings, we would add that it is necessary to include the professionals and service providers involved in recovery efforts. Previous research discusses the need for health care and social service providers, but these efforts must incorporate those working specifically in nonprofit organizations or non-governmental agencies which may take on as much or more disaster relief during a disaster than government agencies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following floods, a negative impact was observed on self-reported life satisfaction in 16 European countries (Luechinger & Raschky, 2009). More recently, following Hurricanes Harvey and Maria in Texas and Puerto Rico, Powell et al (2020) reported high levels of mental distress among health-care and social service workers. But the findings are not unequivocal.…”
Section: Well-being During Traumatic Eventsmentioning
confidence: 99%